If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -13y = 2 Solving 12x + -13y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13y' to each side of the equation. 12x + -13y + 13y = 2 + 13y Combine like terms: -13y + 13y = 0 12x + 0 = 2 + 13y 12x = 2 + 13y Divide each side by '12'. x = 0.1666666667 + 1.083333333y Simplifying x = 0.1666666667 + 1.083333333y
| X^2+(2-k)x-2k=0 | | 12+7r=5+8r | | 2.5p=12.5 | | 4+7a=-8a-11 | | 13+20s=15s+3s-11 | | 9x+5=7x+35 | | 3(4p+7)-9+16= | | 3timesn-5=25 | | -2x+4x=5x+6 | | 6x+52=12x-8 | | x^4-7x^2-44= | | 3*n-5=25 | | 4(z-1)+16=24 | | -40a+28=12 | | 3xn-5=25 | | 0.75p+3=5.88 | | -9-4a=a-2a | | 3y+3=2y-3 | | b/4+9=14 | | (2.72)+2y=3.5 | | 1+9b+6-2b= | | 3r+2=20 | | -40+28=12 | | 9t+4.8=17.4 | | -x-17=-40 | | x-2(2+4)=10 | | K=3M-7forM | | 40x+28=12 | | x-.1x=81 | | 9x-14=4x-4 | | 5Y-10=Y | | -8-6p=-8p+6 |